Values In Balada Cenderawasih Traditional Dance Of Papua: Sociology Of Literature Approach - Casimirus Andy Fenanlampir; Sri Winarsih (Universitas Musamus Merauke, 2019)
Values are considered as motivating guidelines that control people to do things right. There are many categories of values contained in literature and it can be found by learning. Beside that, culture is not just created and genetically passed down from generation to generation but through the process which is called learning. One of interesting traditional dances to learn is Balada Cenderawasih from Papua. It tells a story of Paradise birds and a hunter. Paradise birds are known as one of the protected animals and the ecosystem is many in Papua especially in Wasur National Park in Merauke Papua. This research aims to find out the values in Balada Cenderawasih traditional dance of Papua and to describe how the values relate to the society of Papua. To achieve the objectives, the researchers used sociology of literature approach by Wellek and Warren. Based on the approach, the subjects in this research are the dance and the leader of the studio, as the informant. For the data collection technique, technical triangulation was used by combining frank observation disguised and semi-structured interviews and documentation. For data analysis technique, the analysis model by Miles and Huberman namely data reduction, data display and verification was applied. This study ends with the results showing that values in Balada Cenderawasih traditional dance of Papua include; 1) Aesthetic; it shows the whole contents in the dance deliver particular meaning; 2) Scientific; it reveals that birds has typical life pattern as human; 3) Educational; it teaches people about life; 4) Economic; it portrays human’s behaviour in earning living; 5) Political; it symbolizes leadership and kingdom pattern; 6) Social; it includes moral dan religious values. In fact, studying traditional dance is one of the ways to maintain the culture of native Papuan